Investment promotion and FDI inflows: quality matters - Harding, T; Javorcik, B (University of Oxford, 2012)
Information asymmetries constitute a significant obstacle to capital flows across international borders, and in particular to flows of foreign investment (FDI) to emerging markets. Many governments aim to reduce information barriers by emerging in investment promotion activities. Despite potentially large benefits of FDI and popularity of investment promotion intermediaries (IPIs), relatively little is known about their effectiveness. This study uses data collected through the Global Investment Promotion Benchmarking (GIPB) exercise to examine whether higher quality of IPI services translates into higher FDI inflows. The analysis, based on information on 156 countries, suggests that countries with IPIs able to handle investor inquiries in a more professional manner and IPIs possessing higher quality Web sites tend to attract greater volume of FDI. These results are robust to using sector-level data and instrumental variable approach.